Genetic variation in CARD8, a gene coding for an NLRP3 inflammasome-associated protein, alters the genetic risk for diabetic nephropathy in the context of type 2 diabetes mellitus. (November 2020) - Tsetsos, Fotis; Roumeliotis, Athanasios; Tsekmekidou, Xanthippi; Alexouda, Sophia; Roumeliotis, Stefanos; Theodoridis, Marios; Thodis, Elias; Panagoutsos, Stylianos; Papanas, Nikolaos; Papazoglou, Dimitrios; Kotsa, Kalliopi; Yovos, John G; et al.
Background: Approximately one third of type 2 diabetes mellitus (T2DM) cases present with diabetic nephropathy (DN), the leading cause of end-stage renal disease. Inflammation plays an important role in T2DM disease and DN pathogenesis. NLRP3 inflammasomes are complexes that regulate interleukin-1B (IL-1B) and IL-18 secretion, both involved in inflammatory responses. Activation of NLRP3 is associated with DN onset and progression. Here, we explore whether DN is associated with variants in genes encoding key members of the NLRP3 inflammasome pathway. Methods: Using genome-wide association data, we performed a pilot case-control association study, between 101 DN-T2DM and 185 non-DN-T2DM cases from the Hellenic population across six NLRP3 inflammasome pathway genes. Results: Three common CARD8 variants confer decreased risk for DN, namely rs11665831 (OR = 0.62, p  = 0.016), rs11083925 (OR = 0.65, p  = 0.021), and rs2043211 (OR = 0.66, p  = 0.026), independent of sex or co-inheritance with an IL-1B variant. Conclusion: CARD8 acts as an NLRP3, NF-κB and caspase-1 inhibitor; perhaps, alterations in the cross-talk between CARD8, NF-κB, and NLRP3, which could affect the pro-inflammatory environment in T2DM, render diabetic carriers of certain common CARD8 variants potentially less likely to develop T2DM-related pro-inflammatory responses followed by DN. These preliminary, yet novel, observations will require validation in larger cohorts from several ethnic groups.